1996
DOI: 10.1111/j.1476-5381.1996.tb15608.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and gastric effects of histamine H2 receptor antagonists: no evidence for a correlation between lipophilicity and receptor affinity

Abstract: 1 A series of histamine H2 receptor antagonists with different lipophilicity were tested in cardiac and gastric assays in order to reveal possible differences in receptor affinity. Lipophilicity of the compounds was expressed as CLOG P (theoretically-determined logarithm of octanol:water partition coefficient) and log k' (logarithm of capacity factor, experimentally-determined by reverse-phase high performance liquid chromatography). 2 Aminopotentidine (APT) and iodoaminopotentidine (I-APT), which are both lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…23 On the other hand, ranitidine is a hydrophilic drug and its log (octanol/water partition coefficient for ranitidine) is 0.27. 24 This hypothesis is supported by the in vitro findings of this study that digoxin, but not ranitidine, is well adsorbed by the column.…”
Section: Discussionsupporting
confidence: 66%
“…23 On the other hand, ranitidine is a hydrophilic drug and its log (octanol/water partition coefficient for ranitidine) is 0.27. 24 This hypothesis is supported by the in vitro findings of this study that digoxin, but not ranitidine, is well adsorbed by the column.…”
Section: Discussionsupporting
confidence: 66%
“…First, when preincubations are performed with a mixture of surmountable and insurmountable antagonists, each type of antagonist can counteract the effect of the other in a dose‐dependent fashion. This ability of surmountable agonists to attenuate/alleviate insurmountable inhibition has been well documented for 5‐HT 2 and AT 1 ‐receptors [12–14] and was also noticed for NK 2 tachykinin [15], α 2 ‐adrenergic [16], H 2 histamine [17] and bradykinin B 2 receptors [18]. Moreover, many insurmountable antagonists exhibit intermediary properties with only a partial depression of the maximal response along with a rightward shift of the dose–response curve ().…”
Section: Puzzling Observationsmentioning
confidence: 75%
“…This radiolabel has successfully been used for the labelling of human H 2 receptors in brain tissue (Traiffort et al , 1992). Aminopotentidine (APT) and iodoaminopotentidine (I‐APT) have been shown to behave as insurmountable antagonists of histamine responses in reducing histamine‐induced acid secretion in the anaesthetized rat (Coruzzi et al , 1996). Results obtained in the present study showed that all compounds except analogue F, displaced the specific [ 125 I]‐APT binding to histamine H 2 ‐receptor sites.…”
Section: Discussionmentioning
confidence: 99%